Effect of lyophilization on infectivity and viral load of Adenovirus - Jha, Bimlesh Kumar; Gupta, Birendra Prasad; Maharjan, Prashanna; Kakshapati, Somila; Munankarmi, Nabin Narayan (Nepal Journal of Biotechnology, 2015)
Freeze drying (Lyophilization) performed at temperature and pressure below the triple point is being practiced for the preservation of virus stocks for longer periods. The present study is aimed to lyophilize adenovirus strain to study its effects on infectivity and viral load. In-house adenovirus reference strain (stock virus) was propagated in Hep-2 cell line in 25cm2 cell culture flasks. In 24-well plates the serial dilutions of stock virus from 10-1 to 10-7 (100μl inoculum) was inoculated in each well with Hep-2 cells for TCID50 titer and viral DNA was extracted separately to determine viral load by Taqman Real Time PCR. Stock virus was lyophilized in 3 lots and stored at RT (25±2°C) and 4°C separately for 1, 4 and 6 months and subjected to TCID50 (for viral infectivity) and viral load assay (for total viral genome copies). Following lyophilisation and storage of adenoviral strains at RT and 4°C separately did not affect significantly on the viral stability, infectivity as well as viral copy number till 4 months. However, storage at RT for 6 months resulted in 1 log reduction in viral copy number. Thus, storage of even lyophilized virus stock would necessitate a temperature of at least 4°C for prolonged periods. The present study could successfully lyophilize adenovirus and retain its infectivity over a period of 6 months when stored at RT and 4°C. No significant difference in the infectivity or TCID50 titer was observed in the lyophilized virus as compared to the stock virus. However, the viral load was observed to increase with lyophilization of the virus over 6 months when stored at 4°C which possibly is due to the concentration of the virus on freeze-drying.Nepal Journal of Biotechnology. Dec. 2015 Vol. 3, No. 1: 15-21